Evaluation of receptive and expressive language skills of children with language impairment in Lagos State, Nigeria (2012)
This study examined the receptive and expressive language skills of children with speech/language impairment in three centres in Lagos State, Nigeria, sampling ninety two children between the ages of eighteen months and six years, with evidence of speech/ language defects; using simple random technique. Five research questions generated were tested at 0.05 level of significance, using mean, standard deviations, t- test and Analysis of Variance. The participants were tested with the use of the Preschool Language Scale IV, and a self- deigned questionnaire; with the reliability rate set at 0.82, using the test-retest method. The findings showed that the receptive language skills strength of the participants is higher than their expressive language skills strength; the chronological age and the age equivalent was different; receptive and expressive language equivalent was not gender- sensitive; expressive language skills strength based on neuro- pathological conditions was comparable; and participants exposed to speech therapy have better receptive and expressive language skills than participants without. Based on these findings, it was recommended that help should be sought for the child with suspected deviations from speech/language development, and that the government should establish adequately-equipped early intervention centres in every local government area of the nation.